IN FARABI’S VIEWS, THE IMPORTANCE OF IMAGINATION IN HAPPINESS - Abdufattayeva Shahrizoda Shuhratbek qizi; Ph.D. M. Kadyrov (American Journals Publishing, 2023)
This article reflects the philosophical ideas of Abu Nasr Farabi, who is viewed one of the fantastic thinkers of the Eastern world, about man and happiness, and his thoughts about the importance of imagination in experiencing happiness. Moreover, Farabi's principles of everlasting and general happiness are also reflected.
Keywords: Abu Nasr Farabi, Aristotle, existence, happiness, imagination, man, ideal man, everlasting happiness, standard happiness, proper qualities, bad vices, active mind, divine spirit.